Relearning of Writing Skills in Parkinson's Disease After Intensive Amplitude Training. Issue 8 (17th March 2016) - Nackaerts, Evelien; Heremans, Elke; Vervoort, Griet; Smits‐Engelsman, Bouwien C.M.; Swinnen, Stephan P.; Vandenberghe, Wim; Bergmans, Bruno; Nieuwboer, Alice
ABSTRACT: Background: Micrographia occurs in approximately 60% of people with Parkinson's disease (PD). Although handwriting is an important task in daily life, it is not clear whether relearning and consolidation (ie the solid storage in motor memory) of this skill is possible in PD. The objective was to conduct for the first time a controlled study into the effects of intensive motor learning to improve micrographia in PD. Methods: In this placebo‐controlled study, 38 right‐handed people with PD were randomized into 2 groups, receiving 1 of 2 equally time‐intensive training programs (30 min/day, 5 days/week for 6 weeks). The experimental group (n = 18) performed amplitude training focused at improving writing size. The placebo group (n = 20) received stretch and relaxation exercises. Participants' writing skills were assessed using a touch‐sensitive writing tablet and a pen‐and‐paper test, pre‐ and posttraining, and after a 6‐week retention period. The primary outcome was change in amplitude during several tests of consolidation: (1) transfer, using trained and untrained sequences performed with and without target zones; and (2) automatization, using single‐ and dual‐task sequences. Results: The group receiving amplitude training significantly improved in amplitude and variability of amplitude on the transfer and automatization task. Effect sizes varied between 7% and 17%, and these benefits were maintained after the 6‐week retention period. Moreover, there was transfer to daily life writing. Conclusions: These results show automatization, transfer, and retention of increased writing size (diminished micrographia) after intensive amplitude training, indicating that consolidation of motor learning is possible in PD. © 2016 International Parkinson and Movement Disorder Society